2016
DOI: 10.1017/s0266467416000559
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of recurrent fires on diversity of fruit-feeding butterflies in a south-eastern Amazon forest

Abstract: Abstract:In the south-eastern Amazon, positive feedbacks between land use and severe weather events are increasing the frequency and intensity of fires, threatening local biodiversity. We sampled fruit-feeding butterflies in experimental plots in a south-eastern Amazon forest: one control plot, one plot burned every 3 y, one plot burned yearly. We also measured environmental parameters (canopy cover, temperature, humidity). Our results show no significant differences in overall species richness between plots (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 62 publications
(100 reference statements)
0
13
0
Order By: Relevance
“…In forest environments, we can identify different gradients with distinct origins and effects, among which the most common are forest fragmentation and succession, both usually induced by human activities (Guariguata andOstertag 2001, Fahrig 2013). These gradients have been considered as providing valuable information about the effects of disturbances, such as the consequences of habitat loss, species resistance and resilience to deforestation, and changes in habitat structure (Filgueiras et al 2016, de Andrade et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…In forest environments, we can identify different gradients with distinct origins and effects, among which the most common are forest fragmentation and succession, both usually induced by human activities (Guariguata andOstertag 2001, Fahrig 2013). These gradients have been considered as providing valuable information about the effects of disturbances, such as the consequences of habitat loss, species resistance and resilience to deforestation, and changes in habitat structure (Filgueiras et al 2016, de Andrade et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…We identified indicator species for each fire frequency, suggesting that butterfly species respond differently to variations in fire frequency. Literature suggests that butterfly forest specialists are generally sensitive to fire and can be negatively affected by frequent burning (De Andrade et al 2017). Accordingly, we found that low fire frequency benefits the species that prefer shaded areas in mixed woodland and forest, like the Zulu shadefly (Online Appendix 1 Figure S3).…”
Section: Discussionmentioning
confidence: 55%
“…Indeed, their distributions and population dynamics could be structured by the various plant species composition and structure shaped by different fire regimes (Smit et al 2010;Smith et al 2012). Because of their ecological requirements, butterfly species can be positively affected by frequent fires (Gardiner & Terblanche 2010) or conversely negatively impacted by them (De Andrade et al 2017). As a result, we expect savanna butterflies to be significantly affected by habitat differences that can develop as a result of long-term fire regimes in wetter savannas, from closed to open savanna depending of the fire frequency (Smit et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This can drive abrupt change from forest to derived savannas (40). Cascading effects on a host of forest fauna have been observed, including decline in ant and butterfly communities (40,41) (Fig. 3).…”
Section: Land-use Changementioning
confidence: 99%